Employees' attitudes toward organizational change: A literature review - Choi, Myungweon (Human Resource Management, 2011)
AbstractOrganizations are increasingly required to improve their ability to enhance employees' support or acceptance for change initiatives. In studies that have examined the conditions in which employees support organizational change, researchers have focused on various attitudinal constructs that represent employees' attitudes toward organizational change. The constructs, which frequently serve as key variables in these studies, include readiness for change, commitment to change, openness to change, and cynicism about organizational change. These constructs have distinct meanings and emphases and therefore they can provide us with different information regarding employees' evaluation of and concerns about particular change initiatives. In this literature review, the author discusses how the constructs are defined in the organizational change literature and synthesizes the antecedents of each construct. Based on the discussion, it is proposed that the constructs are susceptible to situational variables, and may change over time as individuals' experiences change; therefore, they are better conceptualized as states than as personality traits. ©2011 Wiley Periodicals, Inc.